1998
DOI: 10.1091/mbc.9.4.957
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-Phase Markers in the Basolateral Endocytic Pathway Accumulate in Response to the Actin Assembly-promoting Drug Jasplakinolide

Abstract: To investigate the role of filamentous actin in the endocytic pathway, we used the cell-permeant drug Jasplakinolide (JAS) to polymerize actin in intact polarized MadinDarby canine kidney (MDCK) cells. The uptake and accumulation of the fluid-phase markers fluorescein isothiocyanate (FITC)-dextran and horseradish peroxidase (HRP) were followed in JAS-treated or untreated cells with confocal fluorescence microscopy, biochemical assays, and electron microscopy. Pretreatment with JAS increased the uptake and accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 51 publications
7
82
1
Order By: Relevance
“…As we observed, high concentrations of jasplakinolide have been reported to increase the density of actin filaments adjacent the plasma membrane in both smooth muscle and Madin-Darby canine kidney cells (25,26), and this is accompanied by the loss of stress fibers in smooth muscle cells (26). Our description of changes in cellular architecture of fibroblasts after jasplakinolide treatment is consistent with those seen in epithelial cells (3).…”
Section: Discussionmentioning
confidence: 65%
“…As we observed, high concentrations of jasplakinolide have been reported to increase the density of actin filaments adjacent the plasma membrane in both smooth muscle and Madin-Darby canine kidney cells (25,26), and this is accompanied by the loss of stress fibers in smooth muscle cells (26). Our description of changes in cellular architecture of fibroblasts after jasplakinolide treatment is consistent with those seen in epithelial cells (3).…”
Section: Discussionmentioning
confidence: 65%
“…n, number of PE analyzed. was described in other cell types, including in T. gondii (Bubb et al, 2000;Shurety et al, 1998;Wetzel et al, 2003). Recently, Smythe et al also observed by immunofluorescence microscopy that treatment of PE with 1 μM JAS for 5 hours caused a cortical redistribution of actin to the parasite periphery (Smythe et al, 2007).…”
Section: The Effects Of Jas and CD On Actin Distribution And Localizamentioning
confidence: 84%
“…However, cytoskeletal materials and peripheral proteins may remain on the cytoplasmic surface with such treatment (Shurety et al 1998;Avery et al 2000;Wetzel et al 2003). Such residue is thought to obstruct observation of the membrane proteins.…”
Section: Membrane Preparation Processmentioning
confidence: 99%